Adoptive Cell Therapy with Tumor-Infiltrating Lymphocytes in Advanced Melanoma Patients - Mélanie Saint-Jean; Anne-Chantal Knol; Christelle Volteau; Gaëlle Quéreux; Lucie Peuvrel; Anabelle Brocard; Marie-Christine Pandolfino; Soraya Saiagh; Jean-Michel Nguyen; Christophe Bedane; Nicole Basset-Seguin; Amir Khammari; et al. (Journal of Immunology Research)
Immunotherapy for melanoma includes adoptive cell therapy with autologous tumor-infiltrating lymphocytes (TILs). This monocenter retrospective study was undertaken to evaluate the efficacy and safety of this treatment of patients with advanced melanoma. All advanced melanoma patients treated with TILs using the same TIL expansion methodology and same treatment interleukin-2 (IL-2) regimen between 2009 and 2012 were included. After sterile intralesional excision of a cutaneous or subcutaneous metastasis, TILs were produced according to a previously described method and then infused into the patient who also received a complementary subcutaneous IL-2 regimen. Nine women and 1 man were treated for unresectable stage IIIC (n=4) or IV (n=6) melanoma. All but 1 patient with unresectable stage III melanoma (1st line) had received at least 2 previous treatments, including anti-CTLA-4 antibody for 4. The number of TILs infused ranged from 0.23 × 109 to 22.9 × 109. Regarding safety, no serious adverse effect was reported. Therapeutic responses included a complete remission, a partial remission, 2 stabilizations, and 6 progressions. Among these 4 patients with clinical benefit, 1 is still alive with 9 years of follow-up and 1 died from another cause after 8 years of follow-up. Notably, patients treated with high percentages of CD4 + CD25 + CD127lowFoxp3+ T cells among their TILs had significantly shorter OS. The therapeutic effect of combining TILs with new immunotherapies needs further investigation.